Student Learning Activity in the Problem Based Learning (PBL) Model for Science Subjects - La Ode Mustafa; Zubair; Siti Nur Hadijah; Meisya (AIQU: Journal Multidiscipliner of Science, 2024)
The fifth-grade students at SDN 3 Katobengke, who engaged well in learning activities, inspired this research. The fifth-grade students were very enthusiastic about learning. When the teacher asked a short question, the students quickly raised their hands to answer. This was evident in their reactions. The next research objective was to determine whether the use of the Problem-Based Learning learning style increases student engagement in science subjects. Furthermore, the researcher was interested in determining the variables that influence the learning activities of fifth-grade students at SDN 3 Katobengke. This research was descriptive qualitative. The following approaches were used to collect data for this study: observation, questionnaires, interviews, and documentation. According to research findings obtained from teacher interviews, children became more engaged when using the Problem-Based Learning pedagogy.